Prevention of adolescent sexual behavior: Can be with family counseling? - Frischa Meivilona Yendi (JRTI (Jurnal Riset Tindakan Indonesia), 2019)
One of the problems that arose in adolescence was juvenile delinquency. One form of juvenile delinquency is sexual behaviour. The handling of sexual behavior in teenagers will not run smoothly if not supported by the parties around the life of youth, i.e. family. If there is one problem in the household, if it continues to be allowed to be dangerous. Settlement of problems in the family can be solved through counseling, which is family counseling.